Application effect of flipped classroom combined with SNAPPS teaching model in emergency medicine interns - Ying Lan; Wang Li (BMC Medical Education, 2026)
Abstract Objective To explore the application value of flipped classroom (FC) combined with SNAPPS teaching framework in emergency department clinical teaching for medical interns. Methods In this randomized controlled trial, a total of 104 fifth-year undergraduate medical interns who were undertaking their clinical rotation in the Emergency Department from 2023 to 2025 were randomly assigned to the reform group ( n = 51, FC combined SNAPPS teaching) and the control group ( n = 53, lecture-based teaching). All participants had completed identical preclinical coursework. The theoretical knowledge scores on admission and discharge, clinical competence (assessed by Mini-CEX), and teaching satisfaction were compared between the two groups. Results No significant between-group difference was observed in theoretical scores at admission ( P > 0.05). At discharge, the theoretical score of the reform group was significantly higher than that of the control group ( P < 0.05), and both groups showed significant improvement compared with admission ( P < 0.05). Mini-CEX scores for clinical competencies (medical history taking, physical examination, condition assessment, and clinical judgment) and scores for four key dimensions of teaching satisfaction (teaching content, learning resources, classroom atmosphere, and teaching methods) were significantly higher in the reform group than in the control group (all P < 0.05). No significant differences were found between the two groups in doctor-patient communication and professional literacy, nor in satisfaction with instructor competence and learning burden (all P > 0.05). Conclusion The FC combined with SNAPPS teaching model can significantly improve the theoretical knowledge and core clinical thinking of emergency medicine interns, as well as enhance teaching satisfaction, which is worthy of clinical promotion.